RURAL FARMERS’ PERCEPTION OF CLIMATE CHANGE IN CENTRAL AGRICULTURAL ZONE OF DELTA STATE, NIGERIA - A.U. Ofuoku (Indonesian Journal of Agricultural Science, 2011)
Farmer perception of their environment is a factor of climate change. Adaptation to climate change requires farmers to realize that the climate has changed and they must identify useful adaptations and implement them. This study analyzed the per-ception of climate change among rural farmers in central agri-cultural zone of Delta State, Nigeria. Climate change studies often assume certain adaptations and minimal examination of how, when, why, and conditions under which adaptations usually take place in any economic and social systems. The study was conducted by survey method on 131 respondents using struc-tured interview schedule and questionnaire. Data were analyzed with descriptive statistics and linear regression model to test that education, gender, and farming experience influenced farmers’ perception of climate change. The results showed that the farmers were aware of climate change. The identified causes of climate change were ranging from intensified agriculture, population explosion, increased use of fossil fuel, loss of in-digenous know practice to gas flaring. The effects of climate change on crops and livestocks were also identified by the rural farmers. Many of the farmers adapted to climate change by planting trees, carrying out soil conservation practice, changing planting dates, using different crop varieties, installing fans in livestock pens, and applying irrigation. Almost half of them did not adapt to climate change. The linear regression analysis revealed that education, gender, and farming experience influ-enced farmers’ perception of climate change. The major barriers to adaptation to climate change included lack of information, lack of money, and inadequate land.